2022
DOI: 10.3390/molecules27051592
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Bioactive Ellagitannins by Ultrasound/Microwave-Assisted Extraction from Mexican Rambutan Peel (Nephelium lappaceum L.)

Abstract: Rambutan (Nephelium lappaceum L.) is a tropical fruit from Asia which has become the main target of many studies involving polyphenolic analysis. Mexico produces over 8 million tons per year of rambutan, generating a huge amount of agro-industrial waste since only the pulp is used and the peel, which comprises around 45% of the fruit’s weight, is left behind. This waste can later be used in the recovery of polyphenolic fractions. In this work, emerging technologies such as microwave, ultrasound, and the hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…casei, and E. durans are tested for the in vitro biodegradation of ellagitannins and the first time that Lacticaseibacillus paracasei, E. faecium, and L.…”
Section: Resultsmentioning
confidence: 99%
“…casei, and E. durans are tested for the in vitro biodegradation of ellagitannins and the first time that Lacticaseibacillus paracasei, E. faecium, and L.…”
Section: Resultsmentioning
confidence: 99%
“…The bioactive molecules were detected by sample injection in high-performance liquid chromatography (Varian ProStar), as reported by Estrada-Gil et al [25]. The samples were filtered through a 0.45 µm nylon membrane with a 1:10 dilution.…”
Section: Phenolic Content By Hplc-esi-msmentioning
confidence: 99%
“…85 In a recent study conducted by Estrada-Gil et al (2022), they confirmed that the simultaneous use of microwaves and ultrasound has a better extraction yield of phenolic compounds from Mexican Rambutan peel residues than the separate use of those techniques. 86 On the other hand, Sillero et al (2020), by optimising the extraction of pine bark by simultaneous use of microwave and ultrasound, concluded that this pre-treatment not only improves extraction yields, but also reduces reaction times by up to 47 times compared to the conventional method. 85 Recently, the use of this pretreatment has also been studied to favour depolymerisation by acid treatment of lignin.…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%